2015
DOI: 10.3892/etm.2015.2287
|View full text |Cite
|
Sign up to set email alerts
|

Study on extracellular matrix metalloproteinase inducer and human epidermal growth factor receptor-2 protein expression in papillary thyroid carcinoma using a quantum dot-based immunofluorescence technique

Abstract: The aim of the present study was to investigate the association of extracellular matrix metalloproteinase inducer (EMMPRIN) and human epidermal growth factor receptor (HER)-2 protein expression in papillary thyroid carcinoma with lymph node metastasis (LNM), as well as the correlation between the two types of protein expression. A quantum dot-based immunofluorescence technique was used to detect EMMPRIN and HER-2 protein expression in 75 papillary thyroid carcinoma cases (including 70 cases of papillary thyroi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 25 publications
(24 reference statements)
2
4
0
Order By: Relevance
“…After a median nine-year follow-up, six patients developed metastatic disease and five of them had HER-2-positive tumors [ 77 ]. The results from Tang et al was consistent with Ruggeri’s study [ 78 ]. The positive HER-2 expression (45.71%) in PTC was significantly associated with lymph node metastatic ( p < 0.05).…”
Section: Hormones and Their Receptorssupporting
confidence: 84%
See 1 more Smart Citation
“…After a median nine-year follow-up, six patients developed metastatic disease and five of them had HER-2-positive tumors [ 77 ]. The results from Tang et al was consistent with Ruggeri’s study [ 78 ]. The positive HER-2 expression (45.71%) in PTC was significantly associated with lymph node metastatic ( p < 0.05).…”
Section: Hormones and Their Receptorssupporting
confidence: 84%
“…HER-2 is an essential marker in the molecular target and prognosis of breast cancer. HER-2 expression in TC was also debatable, varying between 0% and 83.8% [ 76 , 77 , 78 , 79 , 80 ]. In 2001, Kim et al found that HER-2 overexpression in thyroid cancer (83.8%) was more frequent than in benign tumors (16.7%), and was related to the reduction of PTEN protein [ 76 ].…”
Section: Hormones and Their Receptorsmentioning
confidence: 99%
“…GO and KEGG enrichment analysis, establishment of PPI network and network topological analysis were utilized to identify genes potentially related to the initiation and development of PTC. It can be hypothesized that most of the DEGs identified in the present study were enriched in multiple cancer initiation and development-related pathological processes and signaling pathways based on GO and KEGG enrichment analysis from previous research (32)(33)(34)(35)(36)(37). Recent evidence from network biology suggests that genes and proteins do not function in isolation.…”
Section: Discussionmentioning
confidence: 65%
“…Frequently highly overexpressed in malignancies including breast [101], stomach [102], endometrial [103,104], ovarian, uterine [105] colorectal [106], thyroid [107], urothelial [108] Medium levels in glandular cells of appendix, breast, and cervix, myocytes, respiratory epithelium, and urothelial cells [14-16] Table 5. Cont.…”
Section: Retargeting For Binding New Cancer-associated Proteinsmentioning
confidence: 99%